From Evidence to Policy : Supporting Nepal’s Trade Integration Strategy - World Bank Group (World Bank, Washington, DC, 2016)
In the last decades, slow growth and job creation have encouraged emigration, further dampening domestic sources of growth in Nepal. Tepid growth over the past decade, the slowest in the region, has resulted in few jobs being created, leading to more Nepalese workers seeking opportunities abroad. Their remittances have helped reduce poverty in the country and finance increasingly large trade deficits. Like other inflows of foreign exchange, remittances have led to an appreciation of the real exchange rate. This has adversely affected export competitiveness and has had no positive effects on productivity (unlike foreign direct investment). This report attempts to determine the extent to which these obstacles can be alleviated by policy decisions, as well as exactly which policy decisions should be prioritized. The policy notes included in this report aim at supporting the National Trade and Integration Strategy (NTIS) through an evidence-based approach. To do so, these notes combine the following elements: (i) existing analysis on Nepal’s competitiveness from different angles (including existing competitiveness assessments on transport, access to finance, the tourism sector, previous trade competitiveness reports, and so forth); (ii) international experience from comparator countries on good practices for trade policy reforms; (iii) new analysis for Nepal, applying cutting-edge methods on a wide set of databases; and (iv) field-level interviews with the private sector, and consultations with donors and the Government of Nepal.